Effects of Fungicide on Karyomorphology of Lycopersicon Esculentum Mill (Bangladesh Journal of Botany, 2024)
Effect of fungicide on Karyomorphology of three germplasm of Lycopersicon esculentum viz. Acc. No. BD-7748, 7749 and 10125 were investigated in this study. All germplasm treated with different doses of fungicide Ridomil Gold along with control shows different karyomorphological features. Interphase nuclei of these germplasm with different doses were grouped in “Complex chromocenter type”. Prophase chromosomes were “Gradient type” in all germplasm along treated with different doses. All germplasm were found to possess 2n = 24 chromosomes. Fungicide Ridomil Gold has no effect on chromosome number. Seeds treated with water (control) showed much better morphological features whereas different doses of fungicide showed worse result. Therefore, the present investigation showed that fungicide Ridomil Gold has negative effects on karyomorphology of L. esculentum.Bangladesh J. Bot. 53(2): 313-318, 2024 (June)